Student Perceptions on Using ChatGPT as a Translation Tool at Sriwijaya University - Putra, Nito Septian; Amrullah, Amrullah (Journal of English Language and Education, 2026)
This study explored the perceptions of sixth-semester students from the English Education Study Program at Sriwijaya University regarding the use of ChatGPT as a translation tool. With the increasing integration of AI technologies into education, understanding students' experiences and attitudes toward such tools is essential, particularly as empirical studies on students’ perceptions of AI-based translation tools in higher education remain limited. This study employed a quantitative approach using a structured questionnaire that measured four aspects: ease of use, usefulness, effectiveness, and attitude. The participants consisted of 93 students, and the data were analyzed using descriptive statistics. The findings revealed that the students held an overall positive perception of ChatGPT. The highest mean score was found in the ease-of-use category, indicating that students found the tool user-friendly and accessible. The usefulness and attitude categories also received positive responses, while the effectiveness category scored slightly lower, suggesting some limitations in translation accuracy. These results highlight the growing role of AI-based tools in language learning and support the use of ChatGPT as a supplementary translation resource.